Double Marginalization and Vertical Integration - Philippe Choné; Laurent Linnemer; Thibaud Vergé (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Asymmetric information in procurement entails double marginalization. The phenomenon is most severe when the buyer has all the bargaining power at the production stage, while it vanishes when the buyer and suppliers' weights are balanced. Vertical integration eliminates double marginalization and reduces the likelihood that the buyer purchases from independent suppliers. Conditional on market foreclosure, the probability that final consumers are harmed is positive only if the buyer has more bargaining power when selecting suppliers than when negotiating over quantities and intermediate prices. The buyer's and consumers' interests are otherwise aligned.
Keywords: L10; L40; D40; D80; 330; antitrust policy; vertical merger; asymmetric information; bargaining; double marginalization; procurement mechanism